Nanocellulose‐assisted preparation of electromagnetic interference shielding materials with diversified microstructure. Issue 4 (11th May 2022) - Zeng, Zhihui; Qiao, Jing; Zhang, Runa; Liu, Jiurong; Nyström, Gustav
Abstract: Sustainable and renewable nanocellulose attracts more and more attention in various fields due to its high strength‐to‐weight ratio, small diameter, large aspect ratio, and abundant functional groups. The excellent properties and structural characteristics enabled a great potential of nanocellulose for efficient interactions with functional nanomaterials such as carbon nanotube, graphene, transition metal carbides/nitrides (MXenes), and metal nanoparticles, which is beneficial for preparing high‐performance electromagnetic interference (EMI) shields. We review the advances in the nanocellulose‐assisted preparation of composite films and aerogels for EMI shielding application. The nanocellulose‐based composites are evaluated in terms of their EMI shielding performance and the shielding mechanisms, including conduction, polarization, and multiple reflections are summarized. In addition to the constituent structure and contents, we highlight the significance of the microstructure design in enhancing the EMI shielding performance of the nanocellulose‐based EMI shields. Finally, the current challenges and outlook for these fascinating nanocellulose‐based EMI shielding composites are discussed. Abstract : This review summarizes the advances in the nanocellulose‐assisted preparation of composite films and aerogels for electromagnetic interference shielding application, highlights the significance of the microstructure design in performance enhancement, and points out the current challenges and outlook for these fascinating nanocellulose‐based composites.